Analysis of a variable speed air conditioner considering the R-290/POE ISO 22 mixture effect. (5th September 2016) - Ribeiro, Guilherme B.; Barbosa, Jader R.
Highlights: A numerical model that considers the oil-refrigerant mixture effect is proposed. In order to compare the model, an air conditioner calorimeter was constructed. The system was evaluated under oil circulation ratios between 1 and 7%. The presence of oil resulted in a significant SEER deterioration (around 69%). Abstract: Air-conditioning applications using propane (R-290) have several environmental and thermodynamic advantages over more commonly used refrigerants, such as R-410A and R-22. This paper presents the development of a mathematical model for variable capacity air conditioning systems that use R-290/POE ISO 22 as refrigerant/lubricant. The thermodynamic performance of the refrigeration system is evaluated in terms of the SEER (Seasonal Energy Efficiency Ratio). The thermodynamic properties of the refrigerant/lubricant mixture were obtained from a departure-function approach using the Peng-Robinson equation of state. The effect of the oil on the condenser and evaporator heat transfer coefficients and pressure drops was also taken into account. Sub-models were developed for each component of the air conditioning system, including the connecting lines and the scroll compressor. Furthermore, an air conditioner experimental calorimeter was constructed and tested in order to validate the proposed model.